Practice towards Prevention and Control Measures of Coronavirus Disease and Associated Factors among Healthcare Workers in the Health Facilities of the Horo Guduru Wollega Zone, West Ethiopia, 2021. (28th June 2022) - Negera, Atoma; Hailu, Chernet; Birhanu, Addis
Abstract : Background . A novel coronavirus, a virus that causes coronavirus disease (COVID-19), was first identified in Wuhan, China, on December 2019. The virus affects the respiratory system and it is highly contagious, spreading from person to person. Healthcare workers are more at risk due to the nature of their work, which is caring for both COVID-19-affected and nonaffected patients. Lack of knowledge about the disease directly affects early diagnosis and treatment, which may result in the rapid spread of the infection in the community. Having enough knowledge about a disease can always affect an individual's attitudes and practices. However, there is limited evidence on the knowledge, attitude, practice of prevention, and control measures of COVID-19 and associated factors among healthcare workers (HCWs) in resource-limited countries, including Ethiopia. Methods . A facility-based cross-sectional study design was used among 334 samples of health workers who were selected using a stratified two-stage sampling technique, from health facilities of the Horo Guduru Wollega Zone from May to June 2021. A structured self-administered questionnaire was used to collect the data from the HCWs. The information collected was entered to EpiData version 3.1 and exported to SPSS version 21 software for further analyses. Bivariable and multivariable binary logistic regression analyses were used to identify factors associated with the KA practice of the HCWs. Those variables with a p value <05 with a 95% confidence interval (CI) were considered as statistically significantly associated with the outcome variable. Result . Among the participating HCWs, 208 (64%; 95% CI: (58.8%, 69.2%)) of them had good practices of prevention and control measures of COVID-19 with the mean (±SD) practice score was 7.63 ± 2.45. Multivariable binary logistic regression revealed that being a health center worker (AOR = 0.34, 95% CI: (0.19, 0.60)), being trained (AOR = 0.41, 95% CI: (0.21, 0 .82)), and having sufficient knowledge (AOR = 2.73, 95% CI: (1.35, 5.53)) were significantly associated with good preventive practice. Conclusion . The overall magnitude of practice of prevention and control measures of COVID-19 was not sufficient. Therefore, strategies for enhancing the capacity of healthcare workers to exercise practices of prevention and control measures of COVID-19 are needed.